An ionic liquid as a green solvent for high potency synthesis of 2D covalent organic frameworks. (1st September 2020) - Zhao, Limin; Liu, Huimin; Du, Yue; Liang, Xiang; Wang, Wenju; Zhao, Hui; Li, Wenzhi
Abstract : The PXRD and simulated profiles of PMDA–TAPA (a) and TFP–EB (b). Abstract : Covalent organic frameworks (COFs) are emerging crystalline porous materials with a wide range of potential applications. However, optimizing the synthesis process and green synthesis COFs is still a challenge. Here, we report a simple strategy to synthesize two-dimensional covalent organic frameworks (2D COFs) using ionic liquids (ILs) as green solvents. By using the same ILs, 2D keto-enamine-linked COFs and polyimide COFs can be obtained through similar reaction conditions. The structure of the as-synthesized COFs is proved with PXRD, IR and 13 C NMR. The prepared COFs display good crystallinity and high thermal stability. This strategy provides a potential way for the green synthesis of 2D COFs.